Behind the candelabra [videorecording (DVD)] - Soderbergh, Steven, 1963-; Douglas, Michael, 1944-; Damon, Matt (Warner Bros. Entertainment Inc., 2013)
Directed by acclaimed filmmaker Steven Soderbergh and executive produced by Jerry Weintraub, this HBO Films drama recreates the glittering private world of Liberace, the flamboyant, phenomenally successful entertainer whose extravagant costumes, trademark candelabra, and elaborate stage shows made him the most bankable entertainer of his time.